ANALYSING EFL STUDENTS’ ATTITUDE TOWARD ENGLISH AND THEIR INDIGENOUS LANGUAGE IN WEST JAVA - Septianasari, Lina; Toti, Usman Shah (Universitas Muhammadiyah Metro, 2025)
The purpose of this study is to gain a deeper understanding of how EFL students perceive English and their indigenous language in multilingual settings. The participants of this study were EFL students at a private university in West Java, Indonesia, who speak at least two languages, including English and indigenous languages. Participants in the study were given questionnaires and interviews as part of the data collection process. The findings demonstrated that the participants had positive attitudes toward English and their first language. They did not assert that one language was more prestigious or better than the other. The investigation showed that their attitude toward English and their first language was ambivalent. Despite having so close interaction with various languages and cultures, the participants were nevertheless able to keep their native tongue and culture. On one side, the findings showed such relief that the participants were able to maintain their indigenous language. However, the teachers should also be aware of participants’ foreign language acquisition since English and their native language are from different language families.